Inhibition of melanin production and promotion of collagen production by the extract of Kuji amber. Issue 3 (3rd March 2020) - Suzuki, Satoshi; Abe, Junpei; Kudo, Yui; Shirai, Masayuki; Kimura, Ken-ichi
ABSTRACT: Kuji amber is fossilized tree resin of the Late Cretaceous in Japan. In this study, new biological activities of ethanol extract of Kuji amber (EtOH ext.) and supercritical carbon dioxide fluid extract of Kuji amber (scCO2 ext.) were examined. Both EtOH ext. and scCO2 ext. inhibited melanin production in B16 mouse melanoma cells and promoted collagen production in human skin fibroblast SF-TY cells. The scCO2 ext. had more potent activity than that of EtOH ext. and may depend on the efficiency of the extraction. The main new biologically active compound in Kuji amber, kujigamberol had no activities against melanin production, however, it promoted collagen production at low concentrations. A biologically active compound having a different structure, spirolactone norditerpenoid, showed both the inhibition activity against melanin production and the promotion activity of collagen production in a dose dependent manner. EtOH ext. and scCO2 ext., which include both kujigamberol and spirolactone norditerpenoid, have not only anti-allergy activity, but also inhibit melanin production and promote collagen production. Graphical abstract: : The extracts of Kuji amber had inhibition activity of melanin production and promotion activity of collagen activity, with almost the same activity as β-arbutin and L-ascorbic acid. Biologically active compounds were idetified as spirolactone norditerpenoid and kujigamberol.